Star Trek. Volume one, Godshock - Kelly, Collin; Lanzing, Jackson (IDW Publishing, a division of Idea and Design Works, LLC, 2024)
"Stardate 2378: A bold new era of Star Trek begins! Three years ago, Benjamin Sisko made a courageous sacrifice that left him trapped in the dimension of the mysterious Prophets; now he's returned to his home universe--with powerful, godlike abilities. But his omnipotence is failing when he needs it most. Someone is killing the gods, and Sisko and the motley crew of the U.S.S. Theseus will have to travel to the deepest parts of space to stop them"--Provided by publisher